Genes, Parents, and Assisted Reproductive Technologies: ARTs, Mistakes, Sex, Race, & Law - Bender, Leslie (Columbia Journal of Gender and Law, 2003)
A true story: two infertile couples, Donna and Richard Fasano of Staten Island, New York,’ and Deborah Perry-Rogers and Robert Rogers of Teaneck, New Jersey, went to the In Vitro Fertility Center of New York, an in vitro fertilization [hereinafter IVF] clinic in Manhattan, for treatment on the same day in April 1998. Both couples were undergoing IVF procedures that created pre-embryos (“test tube babies”) with hopes of giving birth to their own babies. Due to a clinical error that caused a pre- embryo mix-up that day, Donna Fasano was mistakenly impregnated with as many as six of the Rogerses’ pre-embryos along with at least one of hers and her husband’s pre-embryos’ Deborah Perry-Rogers was also implanted with pre-embryos on April 24, 1998, but all those pre-embryos were hers and her husband’s. Unfortunately, Perry-Rogers’s pre-embryos did not implant in her womb . A few weeks later, on May 28, 1998, after Donna Fasano knew she was pregnant with twins, the clinic notified both couples of the mistake. The Rogerses attempted to learn who had their pre-embryos, but were unable to find out. The Fasanos, on the other hand, did not take any affirmative steps to identify either of their embryos’ genetic parents during Mrs. Fasano’s pregnancy or for several months after the children’s birth. On December 29, 1998, Mrs. Fasano gave birth to two boys, one of whom is European-American like the Fasano couple and the other who is African-American, like the Rogerses. The Fasanos were content to raise both sons, whom they named Vincent and Joseph. However, when the Rogerses learned about the Fasanos’ birth by “luck,” they insisted on having genetic tests done. Those tests revealed that the African-American boy was their genetic child. The Rogerses immediately sued for a declaration of parentage and custody. They also renamed the boy Akeil Richard Rogers. When genetic tests revealed that Joseph/Akeil was the genetic child of the Rogerses, the Fasanos agreed to relinquish custody to the Rogerses, if the Rogerses would execute a written agreement granting them liberal visitation. The agreement, signed on April 29, 1999, gave the Rogerses custody, but contained a carefully delineated visitation schedule and provided for 200,000 in liquidated damages if the Rogerses violated the visitation agreement. Pursuant to that agreement, on May 5, 1999, the Fasanos signed affidavits acknowledging that the Rogerses were Joseph/Akeil’s genetic parents, consenting to the entry of a final order of custody in the Rogerses’ favor, and agreeing to change Joseph/Akeil’s birth certificate. On May 10, 1999, when the baby was four-and-a-half months old, the Fasanos turned the infant over to the Rogerses. The next day the Rogerses complied with the agreement by discontinuing with prejudice the action against the Fasanos (although they retained their action against the IVF clinic).